BACKGROUND VARIABLES AND PREVAILENCE OF BULLYING AMONG SECONDARY SCHOOL STUDENTS IN BAYELSA STATE, NIGERIA - Uche, Rachel D.; Ngwu, Maria E. (IJRDO- Journal of Educational Research, 2016)
This study investigated the extent to which background variables contribute towards prevalence of bullying among secondary school students in Bayelsa State, Nigeria. Three hypotheses were formulated and using a combination of stratified and simple random sampling techniques, 640 secondary school students were selected from ten schools in five out of the eight local government areas (LGAs) of the state. The ex-post facto design was employed and data was collected using a questionnaire titled, Student Bullying Index (SBI). Accruing data was analyzed using Independent t-test and the result indicated significant differences in bullying among students on the bases of school location, parental socioeconomic status (SES) and family type. The conclusion is that there is a high incidence of bullying in the area under study and because bullying has the capacity to place unnecessary strain and stress on students, parents and the educational system, if left unchecked, the following action plan is recommended for school guidance counsellors: Advocacy for good governance; for small sized classes and for improved infrastructure and school facilities, in order to keep students maximally engaged.